Atmospheric implication of synergy in methanesulfonic acid–base trimers: a theoretical investigation. Issue 9 (31st January 2020) - Chen, Dongping; Wang, Weina; Li, Danfeng; Wang, Wenliang
Abstract : The effects of synergy of between X and Y on the stability of MSA–X–Y trimers were investigated via quantum chemical and kinetics simulation method. Abstract : Synergy between molecules is ubiquitous in atmospheric clusters and significantly affects new particle formation (NPF). Herein, the effects of the synergy between base molecules on the stability and evaporation of MSA–X–Y (MSA = methanesulfonic acid; X, Y = ammonia (A), methylamine (M), or dimethylamine (D)) trimers were investigated via density functional theory (DFT) and the atmospheric clusters dynamic code (ACDC) method. The results show that proton transfer from MSA to X is exothermal and barrierless due to the synergy between X and Y molecules in MSA–X–Y trimers compared with MSA-X dimers. Cyclic hydrogen bonds are a typical characteristic of the stable trimers. Topological analysis using atoms in molecules (AIM) theory indicates that the electron density ( ρ ) and Laplacian of the electron density (∇ 2 ρ ) at the bond critical points (BCPs) in the trimers exceed the standard range of hydrogen bonds. The affinity for attaching a Y molecule to the MSA–X dimers and the substitution of Y1 (Y = A and MA) by Y2 (Y2 = MA and DMA) in the MSA–X–Y trimers are thermodynamically spontaneous. In addition, the cyclic stabilization energy of the MSA–X–Y trimers increased as the alkalinities of X and Y increased. The total evaporation rate of the trimers decreased as the alkalinities of X and Y increased. Low temperature and high pressure significantly facilitate the formation of trimers. It is further confirmed that synergy plays an important role in atmospheric NPF events.